The Courtship Art in, Abu Al-Najm Al-Ajli Poetry - عيسى, داليا; عدنان محمد أحمد, (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
Our ancient poetry with its pictorial sources and expressive visions still opens up a wide field for researchers to study and analyze. Our Arab heritage is rich in obscure poets whose pens of scholars left them forgotten, for several reasons. Therefore, this research seeks to unveil one of the undercover men of the Umayyad era, who is the ABU AL-NAJM AL-AJLI, who excelled in many topics of poetry, including courtship, which the research stops at. They did not pay attention to the voice of the nomadic RAJIZ, who was filtered by grief and deprivation. Therefore, the research stops at his courtship and shows the features of the woman’s image as it is the cornerstone of courtship and its main axis.